PERCEPTIONS OF THE IMPLEMENTATION OF THE HARMONIZATION OF TAXATION REGULATIONS (UU HPP), TAX SOCIALIZATION, TAX JUSTICE, AND TAX SANCTIONS ON MSME TAXPAYER COMPLIANCE IN SURABAYA - Dila Alya Putri Kisnawanto (Income, 2024)
This research aims to analyze and determine the influence of perceptions of the implementation of the Harmonization of Taxation Regulations (UU HPP), tax socialization, tax justice, and tax sanctions on MSME taxpayer compliance. This research was conducted on food and beverage MSMEs domiciled in Surabaya and registered with the Surabaya Department of SME Cooperatives and Trade. This research was conducted using a quantitative approach. The research sample was taken through purposive sampling with a total of 110 MSME units. Data were collected using a questionnaire and analyzed using multiple linear regression. The research results explain that perceptions of the implementation of the Harmonization of Taxation Regulations (UU HPP), tax socialization, tax justice, and tax sanctions have a significant positive effect on MSME taxpayer compliance. These results make it clear that the better the perception of MSME taxpayers regarding the implementation of the Harmonization of Taxation Regulations (UU HPP), the better the methods used in socializing taxation, especially those relating to the application of the Harmonization of Taxation Regulations (UU HPP), the fairer the application of tax rates and regulations, and the stricter the sanctions given to taxpayers who violate can increase tax compliance of MSMEs.